2013
DOI: 10.1021/tx300510v
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Exposure to Purity-Controlled Polychlorinated Biphenyl 52, 138, or 180 Alters Toxicogenomic Profiles in Peripheral Blood of Rats after 4 Months

Abstract: It is known from controlled animal experiments and human epidemiologic studies that early life exposure to mixtures of polychlorinated biphenyls (PCBs) is a risk factor for developmental neurotoxicity. The importance of non-dioxin-like PCBs in the context of the observed effect is uncertain because of the blending with the more potent dioxin-like PCBs. Previously, a controlled rat perinatal exposure study with individual, purity-controlled, non-dioxin-like congeners (PCB52, PCB138, or PCB180) was set up. Impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Particularly enriched gene lists in this study included genes of the nervous system development and function ontology. Besides that, enriched pathways included lipid metabolism, molecular transport, small molecule biochemistry, and cell signaling and proliferation [49]. We have to keep in mind, that in this study PBMCs of other species were used and the time of the exposure was in utero.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly enriched gene lists in this study included genes of the nervous system development and function ontology. Besides that, enriched pathways included lipid metabolism, molecular transport, small molecule biochemistry, and cell signaling and proliferation [49]. We have to keep in mind, that in this study PBMCs of other species were used and the time of the exposure was in utero.…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to identify studies in which long lasting changes in lipid metabolism outcomes were analyzed following developmental exposures to PCB. However, in four-month-old rats exposed perinatally to non-dioxin-like PCBs changes in gene expression in blood were significantly enriched for lipid metabolism [38].…”
Section: Discussionmentioning
confidence: 97%
“…One of the closest study design to our work is the gene expression profiles in the peripheral blood of rats exposed to individual NDL congeners (PCBs 52, 138 and 180) at 1 mg/kg during gestation and lactation (De Boever et al, 2013). The authors have found differentially expressed genes belonging to terms involved in lipid metabolism, molecular transport, small molecular biochemistry and cell signaling and proliferation in the peripheral blood of PCB-exposed rats.…”
Section: Discussionmentioning
confidence: 99%